Caracterização morfoquantitativa do corno anterior da medula espinal do sagui (callithrix jacchus) em diferentes faixas etárias e gêneros - Rocha, Laura Laise Pereira da (2019)
The spinal cord is one of the most important neural centers, among its main functions is to promote locomotion. It is scientifically proved that with advancing age this motor function is completely affected. Nevertheless, little is known about the possible morphoquantitative alterations related to motor neuron aging, especially in marmosets, and whether there are distinct responses to gender-related aging. The data related to studies associated with spinal cord quantification are still controversial, since most of them use two-dimensional counting methods, being the main innovation of this work the 3D approach of the possible morphoquantitative changes. This research aimed to investigate the possible morphoquantitative differences of the spinal cord, using stereological delineation techniques during senescence in different genders (males and females). For this, it were used 18 marmosets (Callithrix jacchus), which were divided into 6 groups according to their age groups and genders: young male group (n = 4), male adult group (n = 4), male elderly group (n = 2), female young group (n = 4), female adult group (n = 3) and female elderly group (n = 1). Spinal cords were collected after euthanasia followed by perfusion, systematically, uniformly and randomly sampled and stained using the Nissl protocol. Afterwards, stereological analyzes, were performed where the volumes of the substances (white and gray) of the spinal cord were estimated, as well as the parameters related to the anterior horn: reference volume,neuronal volume, density, total volume, total number of neurons and mean neuronal volume. The results demonstrate that there was a reduction in the gray matter reference volumes in females during aging, as well as a reduction in the anterior horn reference volume regardless of gender. When the volume density was analyzed, there was a reduction in the maturation rocess,while in relation to the total volume of the horn neurons are duction was observed during the maturation and aging process in males. No significant differences were found for the other parameters analyzed